2020
DOI: 10.1177/1071100720938769
|View full text |Cite
|
Sign up to set email alerts
|

Interpositional Arthroplasty With Extensor Digitorum Brevis Tendon in Freiberg Disease

Abstract: Background: No consensus has been reached in the treatment of Frieberg disease. Our aim was to evaluate medium- to long-term results of patients with advanced Freiberg disease managed with extensor digitorum brevis tendon interpositional arthroplasty. Methods: There were 24 patients (19 females, 5 males) managed with interpositional arthroplasty for advanced Freiberg disease between 2003 and 2015. The mean follow-up was 133.8 (range, 60-198) months. According to Smillie classification, there were 4 grade 3, 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…3 Several articles have reported good clinical outcomes of interposition arthroplasty using soft tissue such as the extensor digitorum longus, extensor digitorum brevis, palmaris longus, periosteum with a fat pedicle graft, and allograft of the semitendinosus tendon. [39][40][41][42][43][44] Çevik et al 44 reported the mid-to long-term results of interposition arthroplasty with the extensor digitorum brevis tendon. After a mean follow-up 133.8 (range, 60-198) months, the AOFAS scores improved as did the range of motion in dorsiflexion and plantar flexion.…”
Section: Joint-sacrificing Procedures Interposition Arthroplastiesmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Several articles have reported good clinical outcomes of interposition arthroplasty using soft tissue such as the extensor digitorum longus, extensor digitorum brevis, palmaris longus, periosteum with a fat pedicle graft, and allograft of the semitendinosus tendon. [39][40][41][42][43][44] Çevik et al 44 reported the mid-to long-term results of interposition arthroplasty with the extensor digitorum brevis tendon. After a mean follow-up 133.8 (range, 60-198) months, the AOFAS scores improved as did the range of motion in dorsiflexion and plantar flexion.…”
Section: Joint-sacrificing Procedures Interposition Arthroplastiesmentioning
confidence: 99%
“… 3 Several articles have reported good clinical outcomes of interposition arthroplasty using soft tissue such as the extensor digitorum longus, extensor digitorum brevis, palmaris longus, periosteum with a fat pedicle graft, and allograft of the semitendinosus tendon. 39 - 44 …”
Section: Joint-sacrificing Proceduresmentioning
confidence: 99%
See 1 more Smart Citation